Knowledge, attitudes, and practices of inhalation device use among patients with chronic obstructive pulmonary disease - Yadan Tu; Qiuju Yao; Yong Chen; Yi Ren; Bangjiang Fang; Xuanhan Li; Chenghu Wang; Yigang Wang (Scientific Reports)
Abstract This study aimed to assess the knowledge, attitudes, and practices (KAP) of patients with chronic obstructive pulmonary disease (COPD) regarding inhalation devices. A cross-sectional survey was conducted at Chongqing Hospital of Traditional Chinese Medicine from January to April 2024 among patients with COPD who had been using inhaled medications for at least one month, using a structured questionnaire. Inhaler adherence was evaluated with the Test of Adherence to Inhalers (TAI). A total of 518 COPD patients were enrolled. The average scores for knowledge, attitude, practice, and TAI were 22.82 ± 3.24, 51.79 ± 6.61, 33.08 ± 5.58, and 35.12 ± 11.01, respectively. Correlation analysis demonstrated significant positive relationships between knowledge and attitude (r = 0.490), knowledge and practice (r = 0.368), and knowledge and TAI scores (r = 0.118). Additionally, significant correlations were noted between attitude and practice (r = 0.602) and attitude and TAI scores (r = 0.310). The analysis showed that knowledge directly influenced both attitude and practice and indirectly affected practice through attitude. This study revealed that although COPD patients had adequate knowledge and positive attitude towards inhaler use, their adherence was poor. Tailored educational interventions are recommended to improve adherence to inhalation therapy.